Sarah, plain and tall - MacLachlan, Patricia (New York : Harper & Row, 1985)
When their father invites a mail-order bride to come live with them in their prairie home, Caleb and Anna are captivated by their new mother and hope that she will stay.
"A Charlotte Zolotow book."
Sequel: Skylark.
Keywords: Witting family (Fictitious characters); Stepmothers; Frontier and pioneer life